Improvement of Gypsum Soil by Using Polyurethane to Reduce Erosion and Solubility of Irrigation Canals - Th. Al-Hadidi, Maysam; G. Ibrahim, Atheer (International Journal of Engineering and Technology, 2018)
The reducing of erosion and the solubility of irrigation canals soils which constructed on gypsum soil is important in civil and water resources engineering. The main problem of gypsum soils is the presence of gypsum which represents one of most complex engineering problems, especially when accompanied by the moving of water which represent dynamic load along the canal. There are several solutions to this problem, in this research â€œPoly urethaneâ€ is used to give the gypsum soil sufficient hardness to reduce the solubility and erosion, after compacting the soil in the canal, percentages of Poly urethane was used to making cover to the soil by mixing percent of soil with Poly urethane, and the ratio was as follows: (5 and 10) % and the percent of Poly urethane were as follows: 6%, 10%, and 12%. The collapsibility of the soil was calculated by measuring the height of the soil after the passage of water along the canal. This collapsibility was used as an index to calculate the erosion and the solubility of gypsum within the soil. The results show that the best percentage of poly urethane is (10%), which gave small value in corrosion about (3%) at 28 days.Â Â